PREPARATION AND CHARACTERIZATION OF CHITOSAN BASED SILVER-OXIDE NANOPARTICLES - R. Nagalakshmi; Dr. J. Johncy Caroline; Dr. J. Johncy Caroline (Kongunadu Research Journal, 2025)
Silver oxide nanoparticles (AgO NPs) have attracted significant interest due to their remarkable physicochemical properties, antimicrobial activity, and biocompatibility, making them ideal candidates for a variety of industrial, environmental, and biomedical applications. However, their practical utilization requires stabilization and biocompatibility, which can be achieved by integrating them with natural biopolymers like chitosan. Chitosan, a biodegradable and non-toxic polysaccharide, serves as an effective stabilizer and functionalizing agent, preventing nanoparticle aggregation and enhancing their biological activity. The nanocomposites were synthesized through an eco-friendly approach, with chitosan acting as both a reducing and capping agent. Characterization techniques, including UV, XRD, SEM with EDX, were employed to confirm the formation, size, and dispersion of the silver oxide nanoparticles. In conclusion, chitosan-based silver oxide nanoparticles represent versatile, eco-friendly materials with broad potential for applications. Further research is needed to optimize synthesis methods and enhance nanoparticle stability.